CONVENIENCE SAMPLING: A REVIEW AND GUIDELINES FOR QUANTITATIVE RESEARCH - Mumtaz Ali Memon; Ramayah Thurasamy; Hiram Ting; Jun-Hwa Cheah (Journal of Applied Structural Equation Modelling, 2025)
Convenience sampling is widely used in business and management research, yet its application in quantitative studies is often criticized for lacking rigor and transparency. Despite its prevalence, structured guidance on its responsible use remains limited. This editorial discusses various types of convenience sampling, providing practical examples, outlining its key strengths and limitations, and presenting structured, step-by-step guidelines to support the rigorous application and reporting of convenience sampling in quantitative research. The goal is not to promote this method over probability sampling but to equip researchers, especially those with limited resources or access, with practical tools to enhance the quality and credibility of their research projects.